Randomized Trial of Cytoreductive Surgery for Relapsed Ovarian Cancer. Issue 4 (April 2022) - Harter, Philipp; Sehouli, Jalid; Vergote, Ignace; Ferron, Gwenael; Reuss, Alexander; Meier, Werner; Greggi, Stefano; Mosgard, Berit J.; Selle, Frederic; Guyon, Frederic; Pomel, Christophe; Lécuru, Fabrice; et al.
Abstract : (Abstracted from N Engl J Med 2021;385:2123–2131) Standard of care treatment for advanced ovarian cancer involves primary macroscopic resection of all tumor followed by platinum-based combination chemotherapy with or without additional systemic therapy including bevacizumab or a poly(adenosine diphosphate-ribose) polymerase (PARP) inhibitor. The Descriptive Evaluation of Preoperative Selection Criteria for Operability in Recurrent Ovarian Cancer (DESKTOP) series aims to assess the role of surgery in management of recurrent ovarian cancer.